Edukasi Seks di Kalangan Remaja Perspektif Al-Qur’an dan Hadis: Sebuah Tawaran Prinsip, Materi, dan Metode Aplikatif - Sulaiman; Mahfudz Sidiq (Bulletin of Indonesian Islamic Studies, 2022)
The increase of promiscuity in today's society is already at an alarming level. One of the contributing factors is the stigma of society which considers it taboo to talk about sex among teenagers and children. While in the Qur'an and Hadith a lot of people talk about it. Through qualitative method and library research, authors seek to formulate practical principles, materials, and methods in the process of sex education from the perspective of the Qur'an and Hadith. As a result, to carry out preventive and educative efforts regarding sex, several principles aspects must be strengthened, including; sociological, psychological, and legal principles as well as morals. While the material can be taken from the main material in Islam (Quran and Hadith) as the initial foundation of sex education. Then added with various kinds of general material that is sublimation to sexual "passion". The methods used can be in the form of Quranic and prophetic hiwar methods, Quranic and prophetic stories methods, Quranic and prophetic amsal, and targib wa tarhib.